Combined ultrasound and fluoroscopy guided tunneled external lumbar drain placement in children. Issue 4 (23rd December 2021) - Bertino, Frederic; Shin, David S.; Weaver, John J.; Jeyakumar, Arthie; Chick, Jeffrey Forris Beecham; Woods, Michael A.; Monroe, Eric J.
Abstract: External lumbar drain placement has been shown to be an efficacious and safe approach to managing various forms of intracranial hypertension in adult patients and children. The use of ultrasound guidance for lumbar punctures in young patients has been described however, but the modality is not routinely used for the placement of tunneled lumbar drains. In this report, two cases are presented that detail experience using ultrasound guidance for tunneled lumbar drains in children. Abstract : Ultrasound guidance facilitates tunneled external lumbar drain placement by providing line of sight for the operator and therefore may reduce the number of attempts, traumatic taps, and needle reinsertions or redirections.